2009
DOI: 10.1021/jp902562v
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Hydrophilic Surface Specificity on the Structural Properties of Confined Water

Abstract: The influence of chemical specificity of hydrophilic surfaces on the structure of confined water in the subnanometer regime is investigated using grand canonical Monte Carlo simulations. The structural variations for water confined between hydroxylated silica surfaces are contrasted with water confined between mica surfaces. Although both surfaces are hydrophilic, our study shows that hydration of potassium ions on the mica surface has a strong influence on the water structure and solvation force response of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
99
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(106 citation statements)
references
References 70 publications
6
99
1
Order By: Relevance
“…Experiments under various relative humidity (RH) show that HWL consists of about 6 layers of water molecules on the hydrophilic solid surface. This is thicker than the results of both computer simulation2728 and experiments performed by the AFM-based sharp tip252629, where the results indicate the hydration layer effect on the solid surface disappears at about 3 layers.…”
mentioning
confidence: 56%
“…Experiments under various relative humidity (RH) show that HWL consists of about 6 layers of water molecules on the hydrophilic solid surface. This is thicker than the results of both computer simulation2728 and experiments performed by the AFM-based sharp tip252629, where the results indicate the hydration layer effect on the solid surface disappears at about 3 layers.…”
mentioning
confidence: 56%
“…This range of force is longer than that of the force between silica or mica plates immersed in liquid water (= 12 Å). 49 Interestingly, F z shows a damped oscillation with respect to d: F z is slightly repulsive at the shortest d and reaches a minimum at d = 6 Å at RHs of both 10% and 40% (see below for discussion on why the force is minimal at this d value). This d value at the minimal F z agrees with those found in the GCMC and the density functional theory studies adopting the lattice gas model.…”
Section: Resultsmentioning
confidence: 99%
“…However, similar measurements have shown that the shear viscosity increases by orders of magnitude [12][13][14][15], and simulations have indicated an increase in the translational and rotational correlation lifetimes [16,26]. Computational models of water demonstrate a rich phase behavior consistent with solidification [17][18][19] and dynamical phenomena like shear thinning [10,20] and shear melting and freezing [16].…”
Section: B Shearing Reconstructionsmentioning
confidence: 87%